Morphological and genetic variations of two earthworm species Metaphire bahli (Gates, 1945) and Metaphire peguana (Rosa, 1890) (Oligochaeta: Megascolecidae) in Vietnam - Phan, Thanh Quoc; Nguyen, Duc Anh; Xuan Lam, Truong; Thai, Thi Ngoc Dung; Lam, Hai Dang (Academia Journal of Biology, 2024)
The paper presents the analysis of morphological and genetic variations of two species, Metaphire bahli (Gates, 1945) and Metaphire peguana (Rosa, 1900), from Vietnam. As a result, M. bahli has two morphological forms based on the shape of the male region and state of genital markings while M. peguana has two subspecies, M. peguana peguana, and M. peguana laisonensis. M. peguana peguana had genital markings disc-shaped in 17/18/19 and a diverticulum attached to the base of the ampulla duct while M. peguana laisonensis had genital papillae slit-like shaped in xvii and xix, and diverticulum end at the middle of ampulla duct.